Agricultural Taxation in Pakistan Revisited (The Pakistan Development Review, 1987)
This paper is an attempt to throw further light on the empirical dimensions of the issue of agricultural taxation. 1 It has two objectives: First, using an alternative methodology it attempts to measure the effective tax burden (as opposed to the nominal one) in the agricultural sector (AS) relative to other sectors (NAS): and second, it tries to examine (empirically) the implications of some of the tax proposals made in the literature for various farm groups and, in particular, for tenants. Some of the earlier estimates are either too aggregate or too outdated to be of immediate relevance? Accordingly Sections I and II take the above two points in turn, whereas Section III presents the tentative conclusions of the paper.